Osteoclast generation and cytokine profile at prosthetic interfaces: a study on tissue of patients with aseptic loosening or implant-associated infections: - Dapunt, Ulrike A.; Giese, Thomas; Lasitschka, Felix; Lehner, Burkhard; Ewerbeck, Volker; Hänsch, Gertrud Maria (European journal of inflammation, 2014)
Aseptic loosening of implants or loosening due to persistent bacterial infection remains a severe complication in orthopaedic surgery. To investigate underlying...
Gesehen am 26.10.2020